2021
DOI: 10.1007/s11104-021-04929-6
|View full text |Cite
|
Sign up to set email alerts
|

Living between land and water – structural and functional adaptations in vegetative organs of bladderworts

Abstract: Aims The carnivorous Utricularia (Lentibulariaceae) has an anatomically simple and seemingly rootless vegetative body. It occupies a variety of wetlands and inland waters and shows a broad range of life forms. Here, we aimed to elucidate structural and functional traits in various hydric conditions. Furthermore, we intended to evaluate morpho-anatomical adaptations in correlation with life forms. Methods Morpho-anatomical characteristics typical for hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Thus, together with their taxonomic relevance, forms of leaves and leaf apices are strongly correlated to the habit and in turn to the habitat and water levels. This corroborates the findings of Reut et al (2021),…”
Section: Habit and Reproductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, together with their taxonomic relevance, forms of leaves and leaf apices are strongly correlated to the habit and in turn to the habitat and water levels. This corroborates the findings of Reut et al (2021),…”
Section: Habit and Reproductionsupporting
confidence: 92%
“…(Taylor, 1989;Jobson et al, 2017Jobson et al, , 2018bReut et al, 2021). Reut et al (2021) investigated morpho-anatomical adaptations of Utricularia (including 7 taxa of subgenus Polypompholyx) to submergence and a life in the water column and found that leaves tend to be narrower in submerged hydrophytes and dissected in free-floating hydrophytes, confirming similar observations on heterophyllous amphibious plants (e.g. Nakayama et al, 2017) and obligate hydrophytes (e.g.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations